2016
DOI: 10.2217/nnm-2016-0235
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired artemether-loaded human serum albumin nanoparticles for effective control of malaria-infected erythrocytes

Abstract: Aim: The intra-erythrocytic development of the malarial parasite is dependent on active uptake of nutrients, including human serum albumin (HSA), into parasitized red blood cells (pRBCs). We have designed HSA-based nanoparticles as a potential drug-delivery option for antimalarials. Methods: Artemether-loaded nanoparticles (AAN) were designed and antimalarial activity evaluated in-vitro/in-vivo using Plasmodium falciparum/Plasmodium berghei species, respectively. Results: Selective internalisation of AAN into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
(88 reference statements)
1
9
0
Order By: Relevance
“…3a). This was found to be in good agreement with our previous report (Sidhaye et al, 2016). Polysorbate 80 was also found to have profound effect on entrapment efficiency and drug loading ( Fig.…”
Section: Polysorbate 80 Concentrationsupporting
confidence: 93%
“…3a). This was found to be in good agreement with our previous report (Sidhaye et al, 2016). Polysorbate 80 was also found to have profound effect on entrapment efficiency and drug loading ( Fig.…”
Section: Polysorbate 80 Concentrationsupporting
confidence: 93%
“…Risk assessment studies were performed to identify, analyze, and assess the possible interaction(s) among Mgf, excipients, and other process parameters. Ishikawa fishbone cause-and-affect diagram was constructed and failure mode effect analysis (FMEA) was carried out in order to earmark the critical material attributes (CMAs) and/or critical process parameters (CPPs) for SPNMS of Mgf [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the stability of albumin-based nanoparticles allows the systematic delivery of various agents without degradation [ 10 , 40 ]. In previous studies, it has been shown that the preparation of albumin–artemether NPs through the desolvation method has led to the achievement of nanoparticles with advanced solubility properties and, as a result, increased drug efficiency [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%